Power Quality Improvement in Distribution System Using IRP Theory with SMC - Kalagotla, Chenchireddy; V, Jegathesan (International Journal of Integrated Engineering, 2024)
This article discusses how to improve power quality in distribution systems by combining (Instantaneous Reactive Power) IPR theory with (Sliding Mode Control) SMC. The distribution system has numerous power quality issues. This paper concentrated primarily on source-side current harmonics. The primary goal of this paper is to reduce source-side current harmonics while also balancing DC-link capacitor voltage. The SMC is used to control the d- and q-axis reference currents. The IPR theory is used in distribution to calculate active and reactive power. The SMC based on IPR theory reduced source current harmonics while maintaining constant DC-link capacitor voltage. The results of MATLAB/Simulation are compared to those of PI and SMC. SMC findings exhibit superior performance than the PI controller.